Critical consequences of finding three pathogenic mutations in an individual with recessive disease. Issue 11 (2nd August 2010) - Halsall, Sally; Nicholas, Adeline K; Thornton, Gemma; Martin, Howard; Geoffrey Woods, C
Abstract : The authors report the unexpected finding of three different nonsense mutations in two unrelated individuals with a diagnosis of autosomal recessive primary microcephaly. In each case one phenotypically normal parent was found to carry two of the nonsense mutations, presumably in cis. This finding of 'triple pathogenic mutations' is of unknown incidence but has significant implication for genetic counselling. A failure to detect all three mutations could result in both false positive and false negative diagnoses in other family members. Both of these potential problems can be avoided by always genotyping the parents.